Hypothermia Promotes Interleukin-22 Expression and Fine-Tunes Its Biological Activity - Chichelnitskiy, Evgeny; Himmelseher, Britta; Bachmann, Malte; Pfeilschifter, Josef; Mühl, Heiko (Frontiers in Immunology, 2017)
Disturbed homeostasis as a result of tissue stress can provoke leukocyte responses enabling recovery. Since mild hypothermia displays specific clinically relevant tissue-protective properties and interleukin (IL)-22 promotes healing at host/environment interfaces, effects of lowered ambient temperature on IL-22 were studied. We demonstrate that a 5h exposure of endotoxemic mice to 4°C reduces body temperature by 5.0 degrees and enhances splenic and colonic il22 gene expression. In contrast, tumor necrosis factor (TNF)-a and IL-17A were not increased. In vivo data on IL-22 were corroborated using murine splenocytes and human peripheral blood mononuclear cells (PBMC) cultured upon 33°C and polyclonal T cell activation. Upregulation by mild hypothermia of largely T-cell-derived IL-22 in PBMC required monocytes and associated with enhanced nuclear T-cell NFATc2. Notably, nuclear factor of activated T cells (NFAT) antagonism by cyclosporine A or FK506 impaired IL-22 upregulation at normothermia and entirely prevented its enhanced expression upon hypothermic culture conditions. Data suggest that intact NFAT signaling is required for efficient IL-22 induction upon normothermic and hypothermic conditions. Hypothermia furthermore boosted early signal transducer and activator of transcription (STAT)-3 activation by IL-22 and shaped downstream gene expression in epithelial-like cells. Altogether, data indicate that hypothermia supports and fine-tunes IL-22 production/action which may contribute to regulatory properties of low ambient temperature.